EFFECT OF INBREEDING AND SOME OTHER FACTORS ON AGE AT FIRST CALVING IN GIR COWS (Indian Journal of Animal Production and Management, 2014)
Effects of Inbreeding, sire, period and season on age at first calving (AFC) and its phenotypic and genetic association with other reproductive traits viz., first service period (FSP) and first calving interval (FCI) were studied on 191 Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy Farm, Kasturbagram, Indore (M.P.). The AFC in these cows averaged 1787.46±36.11 days and was significantly (p
Keywords: Age at first calving; inbreeding; Gir